Design of Power Monitoring Security Module for Embedded Device with Elliptic Curve Algorithm - Jeon, Angyoon; Ko, Youngho (International Journal of Engineering and Technology, 2018)
Currently, we are pursuing smart home construction, intelligent living environment, environment-friendly residential living and quality of life. However, power monitoring terminals using various wired and wireless networks and protocols in home networks are very vulnerable to security. In this study, we design and develop security system for smart meter terminal which can analyze the cryptographic technology of smart meter, which is vulnerable to physical attack, and exposes personal information from the outside, and maximize the efficiency of terminal.Â Â